2010
DOI: 10.1002/anie.201002260
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Vesicles through Adaptive Response of a Biobased Surfactant

Abstract: Adaptive response in functional systems of nature is best exemplified by the homeostasis (homeoviscous alterations) or the tropism observed in flora and fauna. The term "homeoviscous alteration" describes the process whereby the fluidity of the membrane is adjusted in response to a perturbation such as temperature, pressure, etc. [1,2] Most of the natural lipids utilize their characteristic unsaturations as a tool to execute such elegant processes. The biophysical properties of the membranes thus depend on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…157,158 The authors reported that the presence of several CH 2 groups was signicant for micelle formation. Balachandran et al 159 described the vesicle formation and vesicular adhesion from a cardanol-based surfactant, N-cardanyl tauramide (NCT) (Fig. 9, S7), obtained by the judicious combination of cardanol as the hydrophobic part and taurine (a vital aminosulfonic acid) as the hydrophilic head group.…”
Section: Surfactantsmentioning
confidence: 99%
“…157,158 The authors reported that the presence of several CH 2 groups was signicant for micelle formation. Balachandran et al 159 described the vesicle formation and vesicular adhesion from a cardanol-based surfactant, N-cardanyl tauramide (NCT) (Fig. 9, S7), obtained by the judicious combination of cardanol as the hydrophobic part and taurine (a vital aminosulfonic acid) as the hydrophilic head group.…”
Section: Surfactantsmentioning
confidence: 99%
“…9). 46 An amide linker was used to facilitate hydrogen-bonded association. At room temperature, a 5 mM aqueous solution of NCT formed micellar aggregates of B8-10 nm diameter (Fig.…”
Section: Surfactants From Cardanolmentioning
confidence: 99%
“…By introducing the aminosulfonic acid taurine into an amphiphilic cardanol system, the nature of the resultant self-assembled system changes [31]. The conditionally essential amino acid taurine facilitates a series of equilibrium processes in mammalian development and imparts similar functionality in micelle, vesicle, and bilayer assemblies of (2) cardanyl tauramide ( Fig.…”
Section: Cardanyl Tauramide's Equilibrative Responsementioning
confidence: 99%
“…Useful to the materials scientist is that the micelles possess distinctly different physical and chemical properties compared to the vesicles that form in heating the solution 30°above room temperature. To confirm the importance of the unsaturations, John et al synthesized an all trans conformation of the pentadecylphenol tauramide from which no viscous phase formed [31]. To recreate cardanol's specific lipid mixture in the lab would have been tedious and costly, and yet by using a naturally occurring mixtures, researchers were able to develop highly functional systems as capable as synthetic alternatives.…”
Section: Cardanyl Tauramide's Equilibrative Responsementioning
confidence: 99%